Report

Lesson 5.2 (PART 2) Functional Notation An equation that is a function may be expressed using functional notation. The notation f(x) (read “f of (x)”) represents the variable y. Functional Notation Cont’d Example: y = 2x + 6 can be written as f(x) = 2x + 6. Given the equation y = 2x + 6, evaluate when x = 3. y = 2(3) + 6 y = 12 Functional Notation Con’t For the function f(x) = 2x + 6, the notation f(3) means that the variable x is replaced with the value of 3. f(x) = 2x + 6 f(3) = 2(3) + 6 f(3) = 12 Evaluating Functions Given f(x) = 4x + 8, find each: 1. f(2) = 4(2) + 8 = 16 2. f(a +1) = 4(a + 1) + 8 = 4a + 4 + 8 = 4a + 12 3. f(4a) = 4(-4a) + 8 = -16a+ 8 Determine the value of x when given f(x). Given f(x) = 4x + 8, determine x when: f(x) = 2 f (x) = -1 Evaluating More Functions If f(x) = 3x 1, and g(x) = 5x + 3, find each: 1. f(2) + g(3) = [3(2) -1] + [5(3) + 3] = 6 - 1 + 15 + 3 = 23 2. f(4) - g(-2) = [3(4) - 1] - [5(-2) + 3] = 11 - (-7) = 18 3. 3f(1) + 2g(2) = 3[3(1) - 1] + 2[5(2) + 3] = 6 + 26 = 32